2016
DOI: 10.17554/j.issn.2311-5106.2016.03.170
|View full text |Cite
|
Sign up to set email alerts
|

Natural History of Lumbar Spondylolysis-Advances and Concerns

Abstract: Lumbar spondylolysis is a common cause of low back pain in adolescents and young adults. Due to a lack of understanding to the natural history, its treatment is often chaotic and controversial. Lumbar spondylolisthesis is a common complication of spondylolysis, but slip progression was commonly small and slow according to long-term follow-up studies. Many predisposing risk factors have been identified as associated with a great chance of slip progression. However, the widely accepted mechanism leading to adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…It is higher in males than in females (2:1). In the American as well as Japanese populations, the incidence was reported to be close to 6%, whereas in the Eskimo, it has reached 50%, and among part of population engaged in certain, high impact sports, it was as high as 63% (Peng, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is higher in males than in females (2:1). In the American as well as Japanese populations, the incidence was reported to be close to 6%, whereas in the Eskimo, it has reached 50%, and among part of population engaged in certain, high impact sports, it was as high as 63% (Peng, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The most frequent is spondylolysis involving the fifth lumbar vertebra L5 (up to 95% of all cases), although it may occur also in other vertebrae from this region, usually with decreasing frequency from the inferior to the superior lumbar spine (Peng, 2016;Wright et al, 2013). If it occurs in more than one vertebra, it is called a multilevel spondylolysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, hereditary predisposition of the vertebral structure (Wynne-Davies and Scott 1979;Yamada et al 2013) and SBO (Fredrickson et al 1984;Wynne-Davies and Scott 1979) have been also suggested as influential factors for developing this pathology. To date, its etiology has been multifactorial, including causes such as a stress fracture linked to congenital weakness of the pars interarticularis in some cases (Krenz and Troup 1973;Peng 2016;Ward et al 2010). SL is asymptomatic in most cases, but back pain may be present, particularly when displacement of the vertebrae occurs, a disorder known as spondylolisthesis (Haun and Kettner 2005), although the etiopathogenesis of both conditions are different (Merbs 1996a).…”
Section: Sacrum Pathologiesmentioning
confidence: 99%